BRIDGING THE GAP BETWEEN ACCOUNTING STANDARDS AND PRACTICE: EVIDENCE FROM SAK EMKM IMPLEMENTATION AMONG MSMES IN TULUNGAGUNG, INDONESIA - Sofi Dwi Ayu Cahyani (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia's economic development; however, many businesses continue to experience difficulties in implementing standardized financial reporting. Although the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) were introduced to simplify financial reporting for MSMEs, empirical evidence regarding their practical implementation at the business level remains limited. This study aims to examine the implementation of SAK EMKM and identify the gap between prescribed accounting standards and actual accounting practices at Hikmah MSME in Tulungagung Regency, Indonesia. A qualitative case study approach was employed using descriptive analysis. Data were collected through interviews, observations, and documentation of the enterprise's accounting records, including purchase records, production reports, fixed asset records, and cash receipt and disbursement documents. The collected data were analyzed by comparing the existing accounting practices with the recognition, measurement, presentation, and disclosure requirements stipulated in SAK EMKM. The findings reveal that Hikmah MSME maintains only basic manual bookkeeping focused on recording cash receipts, cash disbursements, and production costs. The enterprise has not implemented the complete accounting cycle, including ledger preparation, depreciation, financial statement presentation, and disclosures required by SAK EMKM. The implementation gap is primarily influenced by limited accounting literacy, inadequate awareness of SAK EMKM, constrained human resource capacity, and insufficient institutional support. These findings highlight that improving accounting compliance among MSMEs requires not only simplified accounting standards but also continuous technical assistance, accounting education, and stronger institutional engagement to enhance financial reporting quality and support sustainable business development.